2020
DOI: 10.1039/d0ra05615d
|View full text |Cite
|
Sign up to set email alerts
|

Porous lithium cobalt oxide fabricated from metal–organic frameworks as a high-rate cathode for lithium-ion batteries

Abstract: Porous lithium cobalt oxide is fabricated directly from Co-based metal–organic frameworks and lithium salt via a facile solid state annealing approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[152] An obvious 2D-band peak can be observed in the Raman spectrum of the MOF-derived carbon. Meanwhile, the characteristic graphitic XRD peak is much sharper than that of commercial activated carbon, implying the high graphitization ZIF-67 N C V 2 O 5 @C 147@ 1 C, 75.7%@800@5 C LIBs [136] MIL-47(V) V C V 2 O 5 @C 218.1@1 C, 91%@50@0.1 C LIBs [137] V-MOF V C LVP/P-C 65@10 C, 90%@1100@10 C LIBs [138] MIL-101(V) V C LVP@C 144.4@0.1 C, 81%@1000@0.5 C LIBs [139] MnNi-BDC Mn Ni LNMO 121.4@1 C, 83.8%@500@20 C LIBs [140] Fe HKUST-1(Cu) Cu C C@Cu 1.96 S 231@0.2 C, 94%@50@ 0.1 C LIBs [145] NiMn-PMA Ni Mn LNMO 145@0.1 C, 78.7%@500@10 C LIBs [146] NiMn-MOF Ni Mn LNMO 145.3@1 C, 96.9%@500@1 C@40 °C LIBs [147] ZIF-67 Co C LCO@N-C 150.3@10 C,89.1%@200@1 C LIBs [148] ZIF-67 Co LCO 123@0.5 C, 96.4%@100@2 C LIBs [149] ZIF-67 Co LCO/Au foam 155.4@0.2 C, 78.4%@600@2 C LIBs [150] ZIF-4(Co) Co Na 0.74 CoO 2 /C/N 107@0.1 C, 97%@50@5 C SIBs [151] CoZn-ZIF N C NVP@N-C 117@1 C, 87%@10 000@100 C SIBs [152] MIL-101(V) V C NVP@C 136.4@1 C, 84.2%@1000@5 C SIBs [153] ZIF-67 N C NVP/C -, 86.3%@5000 @20 C SIBs [154] V-MOF V C NVP/N-C 117.3@0.1 C, 84%@500@10 C SIBs [155] MIL-125 Ti NTP/rGO 129.2@0.1 C, 91%@250@0.5 C SIBs [156] Fe-MIL-88B Fe C FeOF/C 437.3@0.1 A g −1 , 78%@100@0.1 A g −1 SIBs [157] Fe-MIL-88B Fe C FeF 2 @GC 304.2@50 mA g −1 , 59%@1000@0.3 A g −1 SIBs [158] ZIF-8 N C Mn x O@N-C 192%@120@100 mA g −1 ZIBs [39] MOF-74(Mn) Mn Mn 3 O 4 396.2@0.2 A g −1 , 95.7%@12 000@5 A g −1 ZIBs [159] MnAl-BTC Mn Al Mn 2 O 3 /Al 2 O 3 -, 147.5%@1100@1.…”
Section: Mofs As a Carbon Sourcementioning
confidence: 99%
“…[152] An obvious 2D-band peak can be observed in the Raman spectrum of the MOF-derived carbon. Meanwhile, the characteristic graphitic XRD peak is much sharper than that of commercial activated carbon, implying the high graphitization ZIF-67 N C V 2 O 5 @C 147@ 1 C, 75.7%@800@5 C LIBs [136] MIL-47(V) V C V 2 O 5 @C 218.1@1 C, 91%@50@0.1 C LIBs [137] V-MOF V C LVP/P-C 65@10 C, 90%@1100@10 C LIBs [138] MIL-101(V) V C LVP@C 144.4@0.1 C, 81%@1000@0.5 C LIBs [139] MnNi-BDC Mn Ni LNMO 121.4@1 C, 83.8%@500@20 C LIBs [140] Fe HKUST-1(Cu) Cu C C@Cu 1.96 S 231@0.2 C, 94%@50@ 0.1 C LIBs [145] NiMn-PMA Ni Mn LNMO 145@0.1 C, 78.7%@500@10 C LIBs [146] NiMn-MOF Ni Mn LNMO 145.3@1 C, 96.9%@500@1 C@40 °C LIBs [147] ZIF-67 Co C LCO@N-C 150.3@10 C,89.1%@200@1 C LIBs [148] ZIF-67 Co LCO 123@0.5 C, 96.4%@100@2 C LIBs [149] ZIF-67 Co LCO/Au foam 155.4@0.2 C, 78.4%@600@2 C LIBs [150] ZIF-4(Co) Co Na 0.74 CoO 2 /C/N 107@0.1 C, 97%@50@5 C SIBs [151] CoZn-ZIF N C NVP@N-C 117@1 C, 87%@10 000@100 C SIBs [152] MIL-101(V) V C NVP@C 136.4@1 C, 84.2%@1000@5 C SIBs [153] ZIF-67 N C NVP/C -, 86.3%@5000 @20 C SIBs [154] V-MOF V C NVP/N-C 117.3@0.1 C, 84%@500@10 C SIBs [155] MIL-125 Ti NTP/rGO 129.2@0.1 C, 91%@250@0.5 C SIBs [156] Fe-MIL-88B Fe C FeOF/C 437.3@0.1 A g −1 , 78%@100@0.1 A g −1 SIBs [157] Fe-MIL-88B Fe C FeF 2 @GC 304.2@50 mA g −1 , 59%@1000@0.3 A g −1 SIBs [158] ZIF-8 N C Mn x O@N-C 192%@120@100 mA g −1 ZIBs [39] MOF-74(Mn) Mn Mn 3 O 4 396.2@0.2 A g −1 , 95.7%@12 000@5 A g −1 ZIBs [159] MnAl-BTC Mn Al Mn 2 O 3 /Al 2 O 3 -, 147.5%@1100@1.…”
Section: Mofs As a Carbon Sourcementioning
confidence: 99%
“…The original ideas for LiCoO 2 as a cathode material were inspired by interdisciplinary research in solid-state physics and chemical structure bonding [21]. A study by Wei et al [22] demonstrated that porous LiCoO 2 fabricated from metal-organic frameworks (see Figure 2) show excellent stability and superior rate capability, delivering a reversible capacity of 106.5 mAh g −1 at 2C with a stable capacity retention of 96.4% even after 100 cycles. LiCoO2 has a theoretical capacity of 274 mAh g −1 but often fails to deliver more than half of this due to structural deformation [23].…”
Section: Traditional Cathode Materialsmentioning
confidence: 99%
“…The original ideas for LiCoO2 as a cathode material were inspired by interdisciplinary research in solid-state physics and chemical structure bonding [21]. A study by Wei et al [22] demonstrated that porous LiCoO2 fabricated from metal-organic frameworks (see Figure 1) shows excellent stability and superior rate capability, delivering a reversible capacity of 106.5 mAhg −1 at 2C with stable capacity retention of 96.4% even after 100 cycles. LiCoO2 has a theoretical capacity of 274 mAhg -1 but often fails to deliver more than half of this due to structural deformation [23].…”
Section: Traditional Cathode Materialsmentioning
confidence: 99%